Regular physical activity among obese children: how to prevent the Metabolic Syndrome - Mosca, Antonella; Mennini, Maurizio; Antonetti, Loretta; Piedimonte, Alessandra; Papa, Raffaele Edo; Vania, Andrea (Progress in Nutrition, 2015)
Background: A low level of physical activity (PA) is associated with a regular increase in the risk of Insulin Resistance and Metabolic Syndrome (MS). The aim of our study is to investigate the incidence of MS and alteration of: blood chemistry indices (glucose-lipid parameters, HOMA-IR), blood pressure (BP), Body Mass Index (BMI) and waist circumference/height ratio (W/h), in obese children in relation to the hours of weekly PA. Methods: 915 children (438 M, mean age 10.61 ± 2.79) were divided, into classes according to the number of hours of weekly PA: I (h = 0, 29.40%), II (h = 1-2, 34.10%), III (h = 2-3, 17.15%), IV (h = 3-4, 8.09%), V (h = 4-5, 4.60%), VI (h = 5-6, 3.06%), VII (h>6, 3.60%). Results: The incidence of MS within the classes was: I 6.70 (= 1.97% of the total); II 6.40 (= 2.19%); III 5.70 (= 0.98%); IV 4.00 (= 0.33%); V 7.15 (= 0.33%); VI 17.85 (= 0.55%); VII 3.03 (= 0.11%). Comparing with each class for the contiguous blood indices, PA, BMI Z-and W/h emerges: I Vs. II: W/h, p = 0.0001; PAD p = 0.0001, p = 0.009 PAS; HOMA-IR, p = 0.05; II Vs. III: PAD p = 0.003. Comparing (Student’s t-test) classes I (0 hours AF) and VI (highest incidence of MS) and the other for the indexes is: I: Vs. II W/h, p = 0.0001; III W/h, p = 0.002; The Vs. IV W/h, p = 0.05; The Vs. V W/h, p = 0.02, Z-BMI p = 0.05; The Vs. VI W/h, p = 0.02; The Vs. VII W/h, p = 0.01, p = 0.07 Z-BMI. The vs.VI: Z-BMI p = 0.05; III vs. VI Z-BMI p = 0.03; IV Vs. BMI Z-VI, p = 0.05. The risk of MS in Class I Children is of OR = 5.14, p = 0.02 compared to Class VI and equal to OR=7.17, p=0.04 compared to Class VII. Conclusion: In our population inactive children have a higher risk of MS, altered blood chemistry indices, elevated BP. Also have a worse ratio W/h, even when compared to patients who carry only 1-2 h / week of AF. The reduced abundance of classes V-VII explains the apparent high incidence of MS in class VI.